THE IMPLEMENTATION OF RECIPROCAL TEACHING MODEL TO IMPROVE STUDENTS’ ACHIEVEMENT ON ACID-BASE CONCEPTS - Maysara Maysara; Habiddin Habiddin (J-PEK (Jurnal Pembelajaran Kimia), 2019)
This study aimed to describe the improvement of students’ learning outcomes using reciprocal teaching model. The improvement is measured based on the results of pre-test and posttest. 24 students of XI class at SMA Negeri 4 Wangi-Wangi taking sciences major participated in this study. This one group pre-test & post-test research design used an instrument (test) in the form of multiple-choice questions. The questions were constructed by considering the cognitive level in Bloom taxonomy. The study reveals that students’ improvement falls in the moderate category with the N-gain score of 0.69. The study also uncovered that students’ ability in answering questions decreases with the increase in the cognitive level of the questions